Impact of nutrient management on growth and quality of hybrid chilli (Capsicum annuum) in Typic Haplustalf - GOKUL, D; BHUVANESWARI, R; KARTHIKEYAN, P K; DHANASEKARAN, K; SUGANTHI, S (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2021–22 and 2022–23 at Sivapuri, Chidhambaram taluk, Cuddalore district of Tamil Nadu to evaluate the impact of micronutrient (zinc and boron) fertilization on the growth characters, dry matter production and quality parameters of hybrid chilli (Capsicum annuum Linn.) ‘Mahyco Sierra’ The experiment was laid out in a randomized block design (RBD) with nine treatments and three replications. The treatment included recommended dose of NPK fertilizers (30:60:30 kg N, P2O5 and K2O/ha) combined with zinc and boron fertilizers in different combinations, viz. T1, Control [100% recomended dose of fertilizer (RDF) alone]; T2, RDF + 15 kg ZnSO4/ ha; T3, RDF + 30 kg ZnSO4/ha; T4, RDF + 3 kg borax/ha; T5, RDF + 6 kg borax/ha; T6, RDF + 15 kg ZnSO4/ha + 3 kg borax/ha; T7, RDF + 15 kg ZnSO4/ha + 6 kg borax/ha; T8, RDF + 30 kg ZnSO4/ha + 3 kg borax/ha; T9, RDF + 30 kg ZnSO4/ha + 6 kg borax/ha. The experiment took place on sandy clay loam soil (Typic Haplustalf). Uniform macronutrient fertilizers like nitrogen through urea, phosphors through single super phosphate and potassium through muriate of potash were applied to all the treated plots. The zinc and boron fertilisers were added as soil application as per the treatment. The findings revealed that the maximum values of growth parameters, viz. plant height, number of leaves/plant, number of branches/plant, leaf area index, chlorophyll content and dry matter production (DMP) and quality attributes viz. ascorbic acid content, TSS (total soluble solids) and capsaicin content in fruit were recorded in the treatment of ZnSO4 @30 kg/ha and borax @3 kg/ha (T8) as soil application in both years. However, the control treatment (without micronutrient), the minimum growth characters, dry matter production of plants, and quality parameters in fruit samples were recorded during both the years.